Estratégias de promoção à saúde mental no trabalho de enfermagem hospitalar: revisão integrativa - Santos, Bruna Vasconcelos dos (Universidade Federal de São Carlos, 2023)
Objective: identify strategies for promoting the mental health of hospital nursing workers 2 available in the literature. Method: integrative review developed through access to online information sources. Studies available entirely between 2012 and 2022 in Portuguese, English or Spanish were included. Double-blind selection was carried out, as well as descriptive presentation of results and interpretation in light of the theoretical-conceptual framework. Results: eleven articles point to individual strategies focused on skills training, teleassistance and resilience-building programs that reduced symptoms of depression, anxiety, stress, burnout and turnover, and increased job satisfaction, healthy lifestyles, well-being and general health. Conclusion: strategies for promoting mental health at work maintain their focus on the individual, and do not involve organizational and collective aspects of work, denoting insufficiency by not concentrating on the central causes of the problem. Interventions should be aimed at closing this gap to promote healthier work environments.
Strategies for promoting mental health in hospital nursing work: integrative review
Estrategias de promoción de la salud mental en el trabajo de enfermería hospitalaria: revisión integrativa
Keywords: Estratégias de saúde; Equipe de enfermagem; Hospitais; Saúde ocupacional; Saúde mental; Health strategies; Nursing team; Hospitals; Occupational health; Mental health; Estrategias de salud; Grupo de enfermería; Hospitales; Salud laboral; Salud mental; CIENCIAS DA SAUDE::SAUDE COLETIVA::MEDICINA PREVENTIVA